2014
DOI: 10.1093/ijnp/pyu092
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BDNF, Leptin, and Catecholamines in Reward Learning in Bulimia Nervosa

Abstract: Background:A relationship between bulimia nervosa and reward-related behavior is supported by several lines of evidence. The dopaminergic dysfunctions in the processing of reward-related stimuli have been shown to be modulated by the neurotrophin brain derived neurotrophic factor (BDNF) and the hormone leptin.Methods:Using a randomized, double-blind, placebo-controlled, crossover design, a reward learning task was applied to study the behavior of 20 female subjects with remitted bulimia nervosa and 27 female h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…One comprehensive study on serum BDNF concentrations in a sample comprised of individuals with AN, BN and binge-eating disorder (BED) reported decreased BDNF levels in AN and BN, but not in BED [ 17 ]. Peripheral BDNF concentrations appear to be generally lower in BN [ 81 ] and may recover with therapy [ 82 ], but one study found a significant relationship with reward-related learning in a sample of remitted patients [ 83 ]. Studies on BDNF in other psychiatric conditions including major depressive disorder [ 14 , 84 ] and anxiety in general, and obsessive-compulsive disorder in particular [ 16 ], have similarly reported decreased BDNF levels.…”
Section: Discussionmentioning
confidence: 99%
“…One comprehensive study on serum BDNF concentrations in a sample comprised of individuals with AN, BN and binge-eating disorder (BED) reported decreased BDNF levels in AN and BN, but not in BED [ 17 ]. Peripheral BDNF concentrations appear to be generally lower in BN [ 81 ] and may recover with therapy [ 82 ], but one study found a significant relationship with reward-related learning in a sample of remitted patients [ 83 ]. Studies on BDNF in other psychiatric conditions including major depressive disorder [ 14 , 84 ] and anxiety in general, and obsessive-compulsive disorder in particular [ 16 ], have similarly reported decreased BDNF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Berton and colleagues demonstrated that chronic stress increased BDNF levels within the nucleus accumbens [ 141 ], whereas virally mediated knockdown of BDNF in this region reduced social aversion following chronic social defeat [ 141 ], suggesting that increased BDNF in the ventral tegmental area and nucleus accumbens is positively associated with plasticity-induced aversive learning [ 142 144 ]. Finally, rodents with a knockdown of the BDNF gene in the ventral tegmental area consumed greater amounts of high-fat diet foods [ 145 ], whereas Goto-Kakizaki rats administered intracerebroventricular injections of BDNF exhibited suppressed feeding [ 146 ], a finding that underscores the modulating effects of BDNF on feeding behaviors and its interactions with the mesolimbic dopaminergic reward system [ 147 ].…”
Section: Bdnf In Animal Models Of Depressionmentioning
confidence: 99%
“…Leptin, the product of the obesity gene, is an important hormone involved with feeding behavior, and its concentration in blood is increased in direct proportion to the amount of body fat [ 4 ]. When leptin is carried to the brain through the circulatory system, it is combined with leptin receptors of hypothalamic nerve cells that feeds the regulatory center and sends signals to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…When leptin is carried to the brain through the circulatory system, it is combined with leptin receptors of hypothalamic nerve cells that feeds the regulatory center and sends signals to the brain. This affects energy consumption, the metabolism of carbohydrate and fat, and body weight control [ 4 ]. Active research is examining the association of leptin and feeding behavior, hypothesizing that body weight control is related to obesity, and leptin is being used as the standard evaluating obesity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%